The theory of generality G.E. Zborovsky as a methodological basis for studying the social unit of local self-government - Evgeniy V. Bulakh; Natalia B. Kostina (Муниципалитет: экономика и управление)
Introduction. According to the Russian sociologists, in recent years, domestic sociology has become one of the sciences experiencing a crisis in its development. This is evidenced by the growing criticism of sociological science in society. In sociological science itself, interest in theoretical research is declining even it would seem, in those directions that are capable of revealing the applied nature of sociology. One of the areas is the study of local self-government. A complex social system operates within the boundaries of the municipality. Individual elements of this system are potential participants in local self-government, but so far they have not been identified and described, and their management resources have not been used. Materials and methods. The analytical conclusions are based on the review of theoretical material about the nature of social community. Generalization and assessment of the world scientific experience and the experience of the Greater sociological Urals, of which G.E. Zborovsky is deservedly a prominent representative, allows us to make proposals for expanding the subject part of the sociological theory of communities by substantiating the new category “local community.” The general approach and the theory of generalities involve the use of the following research methods: comparison and contrast, structural-functional, institutional, system analysis, and other methods. Results. The methodological basis, formed on the theoretical views of the Greater sociological Urals group, makes it possible to reveal community-forming properties and supplement this list with those that are characteristic of small territorial communities operating within the boundaries of the municipality. Such communities can be defined as “local communities”, and based on an analysis of their activities in the organizational form of local self-government; they can be compared with a community. A comparison of the categories “local community” and “community” made it possible to identify their similarities, especially in cases where we are talking about self-organized participants in the local community in the form of territorial public self-government. In turn, such an identity reveals prospects for finding answers to questions in interdisciplinary research in the field of local self-government. Rationale and conclusions. The lack of a clear theoretical vision of the municipal social unit that forms the entire municipal community does not allow us to develop and offer a set of applied tools to improve the efficiency of local self-government. “Local community” will fill the gap in the idea of municipal social structure. The presented theoretical additions to the theory of communities allow us to look at the theories of local self-government taking into account the modern description of the community. Taking into account all elements of the local self-government system makes it possible to objectively predict the dynamics of the development of municipal processes with the participation of established local communities.